Understanding the Key Drivers of Systematic Investment Plan Investment Behavior - Shrestha, Sajeeb Kumar; Bhatta, Jagadish (NPRC Journal of Multidisciplinary Research, 2024)
This study aims to examine the key determinants of Systematic Investment Plan (SIP) investment behavior in Nepal, specifically focusing on the relationship between various influencing factors and investment decisions. The study uses both descriptive and causal research designs to explore the connection between factors such as investment behavior, risk tolerance, awareness level, investment objective, and financial freedom with SIP investment. The research was conducted with a sample of 99 young investors from Kathmandu, Nepal, using a structured questionnaire and employing Correlation, and Regression Analysis techniques. The demographic profile of respondents highlights a predominantly young, low-income group engaged in SIP investments, with a significant portion being undergraduates and students. The findings reveal that financial freedom (FF) has the strongest positive correlation with SIP investment, followed by awareness level (AL) and investment objective (IO). In contrast, investment behavior (IB) and risk tolerance (RT) exhibit weaker correlations. Regression analysis further confirms that financial freedom is the most significant predictor of SIP investment behavior, with a notable positive effect. Other variables, such as awareness level and investment objective, while correlated with SIP, do not show statistically significant effects in the regression model. The study underscores the importance of financial freedom and awareness in influencing SIP investment behavior, providing insights into how these factors can be leveraged to promote greater participation in systematic investment plans.